Masalah Belajar Siswa dan Penanganannya - Syafni, Elgi; Syukur, Yarmis; Ibrahim, Indra (Universitas Negeri Padang, 2013)
every student should be free of the problem studied. But in reality there are many students who are still having problems learning, especially in the field of learning skills. This study aims to describe students' learning problems related to learning skills as well as handling. This study classified the type of descriptive quantitative research. The study population of 323 students with a sample of 67 students at SMA N 2 Lintau Buo. The research instrument is the questionnaire. The findings of the research revealed: the high learning problems experienced by students at every skill learning, as well as the lack of interest of students to consult the learning problem faced by teachers BK.